Isolation of the Parasite Enterocytospora artemiae From Chinese Grass Shrimp (Palaemonetes sinensis)—First Report in Asia - Jiang, Hongbo; Chen, Yuwen; Bao, Jie; Li, Xiaodong; Feng, Chengcheng; Xing, Yuenan; Chen, Qijun (Frontiers in Cellular and Infection Microbiology, 2020)
Chinese grass shrimp (Palaemonetes sinensis) is an economically important crustacean in Chinese aquaculture. Recently, we found that shrimp in Panjin city were infected with microsporidia, a group of fungi. The hepatopancreas of several infected shrimp showed white turbidity and pathological changes that negatively affected the health and appearance of the shrimp. Histopathology and transmission electron microscopy were used to examine the development of the parasite within its parasitophorous vacuole. Our results indicated that microsporidia developed asynchronously within the same parasitophorous vacuole. The spores were predominantly small, and rod or oval-shaped. The sizes of fresh spores were approximately 3.1 × 2.4 μm and fixed spores were 1.9 × 1.1 μm. The polar filament was isofilar with 5–6 coils and the thickness was 103.2 nm. Merogonial divisions occurred by binary fission and sporogonial division occurred by plasmotomy. The small subunit ribosomal DNA sequence (1295 bp) from the parasite was highly similar to the previously reported parasite Enterocytospora artemiae (99% nucleotide identity, JX915760). Using maximum likelihood to analyze the phylogenetic relationships, we found that this microsporidian should be grouped within Clade IV, an Enterocytospora-like clade, of the Microsporidia phylum. Based on this parasite’s life cycle characteristics, morphology, and small subunit ribosomal DNA sequence, the parasite described here is likely E. artemiae, which has previously only been described in Europe and North America. Thus, this is the first report of E. artemiae both in Asia and economically important shrimp.